Land reform, latifundia and social development at local level in Colombia, 1961-2010 (2015)
The paper analyzes the effects of land reform on social development -poverty and land distribution- at the local level. Land reform in Colombia, understood as the allocation of public land to peasant, has granted 23 million hectares which comprises around 20% of Colombian territory and about 40% of usable productive land. Theoretically, the net impact of land reform on development is the combination of a poverty effect and a land distribution effect. Our findings suggest that land reform from 1961 onwards has slightly reduced poverty and mildly improved land distribution. Nonetheless, municipalities with strong presence of latifundia prior to 1961 have experienced both a slower drop in poverty and a weaker improvement of land distribution. This paper finds that prevalence of latifundia partially reduces the positive effect of land reform in promoting social development.